The Gospel according to the Epistle of Barnabas Jesus traditions in an early Christian polemic - Edwards, J. Christopher 1982- (Tübingen Mohr Siebeck, 2019)
Wenngleich die Gründe für die ursprüngliche Trennung zwischen Barnabas' Gemeinde und dem gelebten Judentum unwiederbringlich sind, zeigt J. Christopher Edwards in dieser Studie, dass Jesus grundlegend dafür geworden ist, die Trennung zwischen »ihnen« und »uns« aufrecht zu erhalten.
While the reasons for the initial parting of the ways between Barnabas' community and lived Judaism are irrecoverable, J. Christopher Edwards shows that Jesus became foundational for maintaining separation between »them« and »us.« The author undertakes a thorough study of the epistle's Jesus traditions and demonstrates that Jesus is the rhetorical key to almost every argument in this early piece of Adversus Judaeos literature, whether it concerns the law, the covenant, the land, Yom Kippur, circumcision, baptism, the Sabbath, or the temple. No previous work has made the Jesus traditions in Barnabas the focus of its attention.
Keywords: Christology; Jesus; Law; Covenant; Exempla; Thomas Carlyle; Protestant Scholarship On Ancient Judaism; Anti-judaism; Anti-judaism; Neues Testament; Kirchengeschichte